2005
DOI: 10.1007/s10024-004-7077-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Associated with Sudden Infant and Childhood Death

Abstract: Tumors are rare causes of sudden death in infancy and early childhood. The goals of this study were to determine the types and frequency of the tumors associated with sudden death occurring in cases between birth and age 3 years. The San Diego Sudden Infant Death Syndrome/sudden unexplained death in childhood (SUDC) Research Project database and the literature were reviewed retrospectively. Sixty-eight cases, with the most (84%) affecting the heart and brain, were identified. Tumors are a rare but significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have found that infants experiencing ALTEs share some characteristics of the SIDS population in that both groups were predominantly male, and that prematurely born infants, low birth weight babies, and infants with antecedent symptoms were overrepresented [9][10][11]. But ALTEs have many causes including infections, intoxication, head trauma, seizures [12], aspiration of gastric contents [13], cardiac arrhythmias [14], electrolyte imbalance, metabolic disorders, unsafe sleep environments, attempted suffocation [15], and tumors [16], that are neither etiologically nor pathophysiologically related to SIDS and must be excluded before a diagnosis of SIDS can be made. A recent study from Sweden reported that only 1.9% of living control cases in the Nordic pathological study experienced an ALTE compared to 7.4% of the SIDS cases [17].…”
Section: Sids and Altesmentioning
confidence: 99%
“…Previous studies have found that infants experiencing ALTEs share some characteristics of the SIDS population in that both groups were predominantly male, and that prematurely born infants, low birth weight babies, and infants with antecedent symptoms were overrepresented [9][10][11]. But ALTEs have many causes including infections, intoxication, head trauma, seizures [12], aspiration of gastric contents [13], cardiac arrhythmias [14], electrolyte imbalance, metabolic disorders, unsafe sleep environments, attempted suffocation [15], and tumors [16], that are neither etiologically nor pathophysiologically related to SIDS and must be excluded before a diagnosis of SIDS can be made. A recent study from Sweden reported that only 1.9% of living control cases in the Nordic pathological study experienced an ALTE compared to 7.4% of the SIDS cases [17].…”
Section: Sids and Altesmentioning
confidence: 99%
“…The most common primary tumor sites were the heart and the brain, with a majority occurring in the heart (46 of 63), followed by the brain (9 of 63) [14]. Other locations included two bone marrow (leukemia) cases, and one each involving the lung, kidney, mediastinum, pancreas, epiglottis, and thigh [14]. No neuroblastoma cases were present in the study.…”
Section: Discussionmentioning
confidence: 90%
“…In a 2005 study that included a review of the literature for such cases, Krous, Chadwick, and Isaacs found 63 such cases in infants and children up to age 3 years [14]. The most common primary tumor sites were the heart and the brain, with a majority occurring in the heart (46 of 63), followed by the brain (9 of 63) [14]. Other locations included two bone marrow (leukemia) cases, and one each involving the lung, kidney, mediastinum, pancreas, epiglottis, and thigh [14].…”
Section: Discussionmentioning
confidence: 97%
“…Other histopathological types, teratoma, myxoma, and hemangioma, occur much less frequently. 1,3,[8][9][10][11] Primary cardiac angiomyoma in infancy has not been previously reported. Another extremely rare PCT in infancy, also not listed in classifications, is primary cardiac leiomyoma.…”
Section: Discussionmentioning
confidence: 99%